Corrosion engineering boosting bulk Fe50Mn30Co10Cr10 high-entropy alloy as high-efficient alkaline oxygen evolution reaction electrocatalyst. (20th May 2022) - Zhou, Pengfei; Liu, Dong; Chen, Yuyun; Chen, Mingpeng; Liu, Yunxiao; Chen, Shi; Kwok, Chi Tat; Tang, Yuxin; Wang, Shuangpeng; Pan, Hui
Highlights: The self-supported HEA catalyst was prepared by corrosion engineering. Amorphous honeycomb nano-hydroxides are obtained on the HEA surface. HEA-250Ni demonstrates the high OER activity and excellent stability. The excellent performance is due to its special structure and diverse valence states. Our findings open up a new avenue to prepare large-scale HEA as electrocatalysts. Abstract: Oxygen evolution reaction (OER) is a critical process in electrocatalytic water splitting. However, the development of low-cost, highly efficient OER electrocatalysts by a simple method that can be used for industrial application on a large scale is still a huge challenge. Recently, high entropy alloy (HEA) has acquired extensive attention, which may provide answers to the current dilemma. Here, we report bulk Fe50 Mn30 Co10 Cr10, which is prepared by 3D printing on a large scale, as electrocatalyst for OER with high catalytic performance. Especially, an easy approach, corrosion engineering, is adopted for the first time to build an active layer of honeycomb nanostructures on its surface, leading to ultrahigh OER performance with an overpotential of 247 mV to achieve a current density of 10 mA cm −2, a low Tafel slope of 63 mV dec −1, and excellent stability up to 60 h at 100 mA cm −2 in 1 M KOH. The excellent catalytic activity mainly originates from: (1) the binder-free self-supported honeycomb nanostructures and multi-component hydroxides, which improve intrinsic catalytic activity, provide rich active sites, and reduce interfacial resistance; and (2) the diverse valence states for multiple active sites to enhance the OER kinetics. Our findings show that corrosion engineering is a novel strategy to improve the bulk HEA catalytic performance. We expect that this work would open up a new avenue to fabricate large-scale HEA electrocatalysts by 3D printing and corrosion engineering for industrial applications. Graphical abstract: Image, graphical abstract